Effect of structural irregularities on the seismic behavior of reinforced concrete frames - Naveen, E. Siva; Abraham, Nimmy Mariam; Kumari, S.D. Anitha (Journal of Structural Engineering, 2024)
Seismic response of multi-storey buildings depends on the distribution of mass, stiffness, strength and geometry in both horizontal and vertical planes of the building. The irregular configurations either in plan or in elevation may cause severe damage in structural system during earthquake events. Locations of sudden change in mass, stiffness and geometry in structures are weak points. Structures possess combination of irregularities. The consideration of single irregularity may not result in realistic prediction of seismic response. Hence, for the safe design of irregular buildings, it is significant to study the combined effect of irregularities on the response of buildings to dynamic loads. The present work addresses the effect of mass, stiffness and vertical geometry on the seismic response of frames. Twenty one different cases of irregularities along with their combinations were studied and compared. Linear elastic time history analysis was performed to evaluate the seismic response of these structures analytically and the results obtained were then compared with the numerical results obtained from finite element software. The analytical results were observed to follow the same pattern as that of numerical studies. Of all the different frame configurations with irregularities analysed, the configuration with combination of mass, stiffness and vertical geometric irregularity has displayed maximum response whereas the one with mass irregularity alone had shown higher base shear and overturning moment.